Axially‐ and Meso‐Substituted Aza‐Crown‐Ether‐Incorporated BIII Subporphyrins: Control of Electron‐Donating Ability by Metal Ion Chelation. Issue 32 (14th July 2021) - Kise, Koki; Lee, Yu Jin; Tanaka, Takayuki; Kim, Dongho; Osuka, Atsuhiro
Abstract: A series of subporphyrin‐based fluorescent probes bearing 1‐aza‐15‐crown‐5 or 1‐aza‐18‐crown‐6 moieties at the meso or axial positions were prepared by Pd‐catalyzed Buchwald‐Hartwig amination reaction of the corresponding bromosubporphyrins. Both types of aza‐crown‐ether‐incorporated subporphyrins were fluorescent in solution and exhibited cation‐dependent absorption and fluorescence changes. In fluorescence titration experiments, opposite responses were observed for the two types of subporphyrins. Namely, fluorescence quenching occurred for the meso ‐substituted subporphyrins while fluorescence enhancement was observed for the axially‐substituted subporphyrins. These results demonstrate the advantage of subporphyrins being viable to serve as turn‐off‐type or turn‐on‐type fluorescence probes, depending upon substitution pattern. Abstract : Subporphyrins bearing aza‐crown ether moieties at the meso‐ and axial‐positions were synthesized for turn‐off‐ and turn‐on‐type fluorescent chemosensors for metal‐ion detection. Their spectral changes were investigated by titration experiments with seven kinds of metal ions. The fluorescence responses toward metal ions have been controlled by the substitution position and the size of aza‐crown‐ethers.